2009
DOI: 10.1002/mnfr.200800288
|View full text |Cite
|
Sign up to set email alerts
|

Shallot and licorice constituent isoliquiritigenin arrests cell cycle progression and induces apoptosis through the induction of ATM/p53 and initiation of the mitochondrial system in human cervical carcinoma HeLa cells

Abstract: This study is the first to investigate the anticancer effect of isoliquiritigenin (ISL) in human cervical carcinoma HeLa cells. The results reveal that ISL inhibits HeLa cells by blocking cell cycle progression in the G2/M phase and inducing apoptosis. Blockade of cell cycle is associated with increased activation of ataxia telangiectasia-mutated (ATM). Activation of ATM by ISL phosphorylated p53 at Serine15, resulting in increased stability of p53 by decreasing p53 and murine double minute-2 (MDM2) interactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
38
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 39 publications
5
38
0
Order By: Relevance
“…Notably, oral administration of ILQ attenuated the induction of preneoplastic aberrant crypt foci in the colon of male F344 rats [59]. This licorice compound abrogated G2/M cell cycle progression and effectively induced apoptosis in HeLa human uterine cervical cancer cells [62]. Investigators observed activation of ataxia telangiectasia-mutated (ATM), increased phosphorylation of p53 (Ser15) and changes in several cell cycle proteins, including cyclin B, cyclin A, cell division cycle protein (Cdc)2, cdc25C, and checkpoint kinase (Chk)2.…”
Section: Iso-liquiritigeninmentioning
confidence: 90%
See 1 more Smart Citation
“…Notably, oral administration of ILQ attenuated the induction of preneoplastic aberrant crypt foci in the colon of male F344 rats [59]. This licorice compound abrogated G2/M cell cycle progression and effectively induced apoptosis in HeLa human uterine cervical cancer cells [62]. Investigators observed activation of ataxia telangiectasia-mutated (ATM), increased phosphorylation of p53 (Ser15) and changes in several cell cycle proteins, including cyclin B, cyclin A, cell division cycle protein (Cdc)2, cdc25C, and checkpoint kinase (Chk)2.…”
Section: Iso-liquiritigeninmentioning
confidence: 90%
“…Investigators observed activation of ataxia telangiectasia-mutated (ATM), increased phosphorylation of p53 (Ser15) and changes in several cell cycle proteins, including cyclin B, cyclin A, cell division cycle protein (Cdc)2, cdc25C, and checkpoint kinase (Chk)2. Apoptosis corresponded with changes in pro-apoptotic Bax and Bak and decreased levels of antiapoptotic Bcl-2 and Bcl-XL in HeLa cells [62]. Interestingly, ILQ could inhibit in vivo lung metastasis of MDA-MB-231 breast cancer cells by preventing resistance to anoikis [63•], which is a type of apoptosis induced by anchorage-dependent cells detaching from the extracellular matrix around them [64].…”
Section: Iso-liquiritigeninmentioning
confidence: 99%
“…Radical surgery or radiotherapy can be curative for the majority of patients with early-stage cervical cancer; however, chemotherapy is always the first choice for patients with the advanced disease for which the prognosis remains very poor (Zhang B et al, 2006;Li et al, 2009;Kim et al, 2010;Al-Hazzani and Alshatwi, 2011;Ju et al, 2012;Alshatwi et al, 2013;Ramesh and Alshatwi, 2013;Zhu et al, 2013;Jin et al, 2014). Although the platinumor taxane-based chemotherapy either neoadjuvant before surgery or combined with radiotherapy can significantly improve the survival of patients, the success of these treatment modalities is often hindered by emerging of chemoresistance and/or radioresistance as well as by severe lethality on normal cells resulting in serious toxicity (Hsu et al, 2009;Koppikas et al, 2010;Singh et al, 2010;Liu et al, 2012;Chen et al, 2013b;Chen et al, 2013a;Lo et al, 2013;Singh et al, 2013;Zhu et al, 2013). Therefore, the survival benefit of conventional therapies is limited, relapse can occur after treatment, and cervical cancer continues to have one of the lowest five-year survival rates being only about 52% (Hsu et al, 2009;Singh et al, 2010;Chen et al, 2011;Zeng et al, 2012a;Kim and Kim, 2013;Singh et al, 2013).…”
Section: Characteristic Features Of Cytotoxic Activity Of Flavonoids mentioning
confidence: 99%
“…Although the platinumor taxane-based chemotherapy either neoadjuvant before surgery or combined with radiotherapy can significantly improve the survival of patients, the success of these treatment modalities is often hindered by emerging of chemoresistance and/or radioresistance as well as by severe lethality on normal cells resulting in serious toxicity (Hsu et al, 2009;Koppikas et al, 2010;Singh et al, 2010;Liu et al, 2012;Chen et al, 2013b;Chen et al, 2013a;Lo et al, 2013;Singh et al, 2013;Zhu et al, 2013). Therefore, the survival benefit of conventional therapies is limited, relapse can occur after treatment, and cervical cancer continues to have one of the lowest five-year survival rates being only about 52% (Hsu et al, 2009;Singh et al, 2010;Chen et al, 2011;Zeng et al, 2012a;Kim and Kim, 2013;Singh et al, 2013). Consequently, the development of more effective, highly selective and less toxic anticancer agents as well as novel therapeutic intervention strategies are needed to improve the treatment success and reduce the cervical cancer morbidity and mortality rate.…”
Section: Characteristic Features Of Cytotoxic Activity Of Flavonoids mentioning
confidence: 99%
See 1 more Smart Citation